2020
DOI: 10.1136/bmjopen-2019-034046
|View full text |Cite
|
Sign up to set email alerts
|

Identifying significant contributors for smoking cessation among male prisoners in Australia: results from a randomised clinical trial

Abstract: IntroductionIn Australia, an estimated 90% of those entering prison are current tobacco smokers and three-quarters of current prisoners are tobacco smokers.AimsTo identify factors and their relative contributions to smoking cessation among male prisoners.MethodsA total of 425 male tobacco smokers with a median age of 32 years in Australian prisons. The primary outcome was continuous abstinence at 3, 6 and 12 months. We measured various sociodemographic characteristics, drug use, psychological distress and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
1
0
1
Order By: Relevance
“…In the case of prisoners, 25.8% declared smoking, i.e., less than in the report of the National Health Account of Poles in 2020, which showed that the percentage of active smokers of all tobacco products is 32% [ 37 ]. Wand et al showed that three-quarters of current prisoners in Australia are tobacco smokers [ 38 ]. Smoking is a learned habit and a major preventable chronic disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of prisoners, 25.8% declared smoking, i.e., less than in the report of the National Health Account of Poles in 2020, which showed that the percentage of active smokers of all tobacco products is 32% [ 37 ]. Wand et al showed that three-quarters of current prisoners in Australia are tobacco smokers [ 38 ]. Smoking is a learned habit and a major preventable chronic disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ces composantes complémentaires prévoient la diffusion d'informations adaptées concernant les risques du tabac, les bénéfices de l'arrêt et les méthodes d'arrêt existantes (8,24,25), un accès facilité aux substituts nicotiniques (8,24,25), la mise en place d'actions de soutien psychologique et d'activités de compensation pour remédier au manque et à l'ennui (25,26), ainsi que l'aménagement de zones sans tabac (13)(14)(15).…”
Section: Les Interventions Multi-composantes Ont Démontré Leur Efficacité Auprès Des Personnesunclassified